2001
DOI: 10.1046/j.1365-2249.2001.01465.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of CMV on the respiratory burst of macrophages in response toPneumocystis carinii

Abstract: SUMMARYInfection of human monocyte-derived macrophages with CMV decreased the respiratory burst when cells were stimulated with opsonized zymosan or Pneumocystis carinii (P. carinii). Such an effect, though smaller, was also seen with heat-inactivated CMV, but only when triggered by zymosan. The effect was most pronounced in cells obtained from CMV antibody-negative donors. Dexamethasone further reduced the respiratory burst, both in uninfected and CMV-infected cells. Interferon-g increased the response in uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Other potential mechanisms include the immune-modulating effects of the virus itself: CMV can impair multiple antimicrobial effector mechanisms, including neutrophil activity and macrophage respiratory burst. 42,43 Results of recent studies that emphasized poor transplant outcomes associated with donor or recipient CMV seropositivity provide compelling evidence for direct effects of the virus. In one study, higher transplant-related mortality (TRM) was observed in CMV-seropositive recipients of T cell-depleted grafts than in CMV-seronegative recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Other potential mechanisms include the immune-modulating effects of the virus itself: CMV can impair multiple antimicrobial effector mechanisms, including neutrophil activity and macrophage respiratory burst. 42,43 Results of recent studies that emphasized poor transplant outcomes associated with donor or recipient CMV seropositivity provide compelling evidence for direct effects of the virus. In one study, higher transplant-related mortality (TRM) was observed in CMV-seropositive recipients of T cell-depleted grafts than in CMV-seronegative recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies using animal models have shown that CMV infection inhibits immune responses against P jirovecii , and contributes to delayed clearance of the organism. [ 25 , 26 ]…”
Section: Discussionmentioning
confidence: 99%
“…Other potential mechanisms included the immune-modulating effects of CMV itself, because this virus is known to impair neutrophil activity and macrophage respiratory burst. 41,42 Alternatively, clinical factors included in multivariable models might not adequately control for the immune variables that predicted both CMV and fungal infections.…”
Section: Discussionmentioning
confidence: 99%